THE EFFECT OF KNOWLEDGE SHARING, ABSORPTIVE CAPACITY, AND INDIVIDUAL CREATIVITY ON INNOVATION PERFORMANCE IN EAST JAVA INDONESIA MANUFACTURING COMPANIES - Inggrid Elier; Prita Ayu Kusumawardhany; Antonius Budhiman Setyawan (UNUSA Press, 2022)
This study aims to determine the effect of knowledge sharing, absorptive capacity, and individual creativity on innovation performance in manufacturing companies in East Java. This writing is quantitative writing with the SEM (Structural Equation Modeling) data processing method using SPSS 23.0 software to test the validity and reliability at an early stage and using PLS 3.0 software to test the research model. This writing method was carried out by distributing online questionnaires to 150 respondents in East Java who carried out knowledge sharing, absorptive capacity, individual creativity, and innovation performance activities in manufacturing companies. The sample used in this paper is the owner, director, manager, or department head of an East Java manufacturing company. The results of this study will show several factors that have a significant positive effect on innovation performance.